Saddle Point and Second Order Optimality in Nondifferentiable Nonlinear Abstract Multiobjective Optimization - Santos, Lucelina Batista dos; Rojas-Medar, Marko Antonio; Oliveira, Valeriano Antunes de [UNESP] (Brazilian Society for Computational and Applied Mathematics (SBMAC), 2012)
This article deals with a vector optimization problem with cone constraints in a Banach space setting. By making use of a real-valued Lagrangian and the concept of generalized subconvex-like functions, weakly efficient solutions are characterized through saddle point type conditions. The results, jointly with the notion of generalized Hessian (introduced in [Cominetti, R., Correa, R.: A generalized second-order derivative in nonsmooth optimization. SIAM J. Control Optim. 28, 789–809 (1990)]), are applied to achieve second order necessary and sufficient optimality conditions (without requiring twice differentiability for the objective and constraining functions) for the particular case when the functionals involved are defined on a general Banach space into finite dimensional ones.

O artigo trata de um problema de otimização vetorial entre espaços de Banach com restrições envolvendo cones. Usando-se uma lagrangiana que toma valores escalares e o conceito de funções subconvexas generalizadas, soluções fracamente eficientes são caracterizadas por condições do tipo ponto de sela. Os resultados, em conjunto com a noção de Hessiana generalizada (introduzida em [R. Cominetti, R. Correa, A generalized second-order derivative in nonsmooth optimization, SIAM J. Control Optim., 28 (1990), 789–809]), são aplicados para se obter condições necessárias e suficientes de segunda ordem para o caso particular em que as funcionais envolvidas são definidas em um espaço de Banach geral mas com valores em espaços de dimensão finita (sem exigir que as funções objetivo e de restrições sejam duas vezes diferenciáveis).
Keywords: Multiobjetive optimization; abstract optimization problems; nonlinear programming; saddle point conditions; generalized second order conditions; generalized convexity